Eksistensi Al-Ibrah (Pemutihan Piutang) Pada Bank BNI Syariah Cabang Kendari - Husain Insawan; Mutmainnah Mutmainnah (Li Falah: Jurnal Studi Ekonomi dan Bisnis Islam, 2018)
This study aims to determine the perceptions of employees of the BNI Syariah BankBranch of Kendari regarding the concept of al-Ibrah, as well as to investigate theexistence of Al-Ibrah it has been implemented or not. Sharia Commercial Banks in Indonesia are growing promising in the future. Thirteen Sharia Commercial Banks have been recorded. But there is one action that is not yet familiar to do, which is doing Al-Ibrah or bleaching of receivables. BNI Syariah Branch employees still have a cross opinion about this concept. This action is actually legally guaranteed through the DSN-MUI Fatwa No. 47 / DSN-MUI / II /2005 concerning Settlement of Murabahah Receivables for Customers Who Are Not Able to Pay. Kendari Branch BNI Syariah as part of the Sharia Commercial Bank is not in a position to reject the existence of Al-Ibrah, but to avoid it from the outset the principle of caution has been applied in offering financing products through Musyarakah, Mudharabah, Murabahah, Istishna, or borrowing through Qardh